2018
DOI: 10.1016/j.jds.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine is a risk factor for dental caries: An in vivo study

Abstract: Background/purpose Streptococcus mutans is an important pathogen in the development of dental caries. Many studies have focused on the relationship between nicotine and S. mutans in vitro . The aim of this study was to investigate the effect of nicotine on the growth of S. mutans and its cariogenic potential in vivo . Materials and methods Sixteen male Specific-pathogen-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…These increased virulence factors of S. mutans may be responsible for the increased cariogenicity of S. mutans in experimental rats fed 1 mg/mL of nicotine (Liu et al 2018). Several reports indicate the destructive oral and systemic effects of smoking and nicotine exposure, leading to development or exacerbation of dental caries and heart diseases such as atherosclerosis (Wagenknecht et al 2018).…”
Section: Effect Of Nicotine On Streptococcus Mutansmentioning
confidence: 99%
“…These increased virulence factors of S. mutans may be responsible for the increased cariogenicity of S. mutans in experimental rats fed 1 mg/mL of nicotine (Liu et al 2018). Several reports indicate the destructive oral and systemic effects of smoking and nicotine exposure, leading to development or exacerbation of dental caries and heart diseases such as atherosclerosis (Wagenknecht et al 2018).…”
Section: Effect Of Nicotine On Streptococcus Mutansmentioning
confidence: 99%
“…Experimental evidence supports a positive association between second-hand smoke exposure and dental caries. An in vivo study found that nicotine increased the attachment of cariogenic bacteria, Streptococcus mutans on the nicotine-treated rats' teeth surfaces [47]. Elevated level of Streptococcus mutans was found in human who exposed to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated level of Streptococcus mutans was found in human who exposed to cigarette smoke. High amount of Streptococcus mutans can secrete more extracellular polysaccharides that lower the pH value of the biofilm on the surfaces of the teeth, which in turn increased demineralization [47]. Furthermore, second-hand smoke decreased the mineralisation of tooth, the rate of salivary flow, and impaired immunity, which led to the colonisation of cariogenic bacteria in teeth [48].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine upregulates certain S. mutans virulence genes including GTF and glucan binding protein (GbpA) expression, and Ldh, nlmC, and phosphotransferase system (PTS)-associated genes, which eventually leads to more lactic acid production [5,6]. A recent in-vivo study indicates that caries was higher in Wistar rats infected with S. mutans and treated with nicotine compared with a nicotine-untreated group [7].…”
Section: Introductionmentioning
confidence: 99%